1. The problem statement, all variables and given/known data Find the solution to :y''+2y'+y=t 2. Relevant equations Suppose y(t)=B1t2+B2t+B3 And I believe, Y(t)=Yh+Yp. That is the solution is equal to the solution to the homogenous equation, plus the particular solution. 3. The attempt at a solution First Solve the homogeneous equation: y(t)=B1t2+B2t+B3 y'(t)=2B1t+B2 y''(t)=2B1 Substitute this back into the homogenous problem(y''+2y'+y=0) gives: 2B1+2(2B1t+B2)+B1t2+B2t+B3=0 Rearrange: B1(t2+4t+2) +B2(t+2)+B3=0 Solution is t=-2 or B1,B2,B3=0 Now I'm unsure of what to do? As for the particular solution say Yp: Yp=ct, where c is a constant so, Y'p=c Y''p=0 Substitute this into :y''+2y'+y=t 0+2c+ct=t c=? Thanks for any help.